Beyond reading. (2nd April 2022) - Baker, Charlotte
Abstract : Charlotte Baker explores how to holistically approach reading time, looking at some of the possibilities of changing up reading activities in order to keep children's engagement high and to foster other types of learning; from using emotional intelligence to begin to understand how some of the characters are feeling to the sensory experiences of creating and using musical instruments.